Gambaran Pola Makan Remaja dan Status Gizi di SMA Swasta Katolik Budi Murni 2 Medan Tahun 2023 - Siringo-ringo, Magda; Tapoleuru, Teresia Nosrat (JURNAL KEPERAWATAN MERSI, 2023)
Background: Nutritional status is a condition caused by a balance between the intake of nutrients from food with the needs of nutrients needed for the body's metabolism. Nutritional status in adolescents often experience food intake, causing nutritional imbalances in the body. Adolescents who are malnourished will cause the body's immune system to become weak so that it is susceptible to disease, especially the risk of infectious diseases and non-communicable diseases. Imbalance of food consumed with the needs in adolescents can cause nutritional problems, both undernourished and overnourished. Based on an initial survey of adolescents at Budi Murni 2 Catholic Private High School Medan, it was found that the nutritional status was less than 20%. Objective: This study aims to determine the picture of adolescent diet with nutritional status at Budi Murni 2 Catholic Private High School Medan in 2023. Methods: This study was descriptive with a cross-sectional design. The population is 425 people, with a sample of 70 people, using simple random sampling techniques. Data collection using interview and observation techniques using questionnaires. Results: The results of the study found that the diet of adolescents staple foods with sufficient categories was 62.9%, animal side dishes in the sufficient category by 67.1%, sufficient vegetable side dishes by 68.6%, sufficient vegetables by 51.4%, sufficient fruits by 51.4%, more snacks by 50.0% and sufficient drinks by 62.9% while the nutritional status of the normal category was 58.6%. Conclusion: It is expected that adolescents can regulate a good and regular diet by eating three times a day and consuming staple foods, side dishes, vegetables, fruits and water in a balanced manner.